Study on the natural gas pipeline safety monitoring technique and the time-frequency signal analysis method. (May 2017) - Qu, Zhigang; Wang, Yanfen; Yue, Huanhuan; An, Yang; Wu, Liqun; Zhou, Weibin; Wang, Huayang; Su, Zhichao; Li, Jian; Zhang, Yu; Wang, Likun; Yang, Xiliang; et al.
Abstract: Hydrate plugging and leakage in natural gas pipelines have been big issues for the industry with the globally increasing demand for natural gas. A natural gas pipeline safety monitoring technique is studied in this paper, which is based on acoustic excitation. In this technique hydrate plugging and leakage can be monitored online at multiple locations and distinguished by "energy-pattern" method based on the wavelet packet analysis. The position of a hydrate plugging or leakage can be achieved by correlation algorithm. The results of experiments and modeling work show that the technique can locate hydrate plugging or leakage at multiple positions with good accuracy and distinguish them effectively. Highlights: The method is able to monitor and locate both hydrate plugging and leakage online at multiple locations in a gas pipeline. A time-frequency signal analysis method based on wavelet packet has been proposed and proven to be able to distinguish hydrate plugging and leakage effectively. A hydrate detection model for long range gas pipe has been presented.